1998
DOI: 10.1016/s0022-5223(98)70365-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic assessment of nerve impairment in posterolateral and muscle-sparing thoracotomy

Abstract: This study shows for the first time the pathophysiologic differences between posterolateral and muscle-sparing thoracotomy and suggests that the minor long-lasting postthoracotomy pain in muscle-sparing thoracotomy patients is partly due to a minor nerve damage. In addition, because nerve impairment is responsible for the long-lasting neuropathic component of postoperative pain, it is necessary to match specific treatments to the neuropathic pain-generating mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(106 citation statements)
references
References 18 publications
1
90
0
13
Order By: Relevance
“…These nerves may be injured during surgical incision, rib retraction, trocar placement, or suturing. 5,6 Post-thoracotomy pain syndrome is typically described as aching or tenderness and is localized to the area of incision in approximately 82% of cases. 7 Chronic postthoracotomy pain remains a challenge for clinicians, as many treatment and prevention strategies have yielded disappointing results.…”
Section: The International Association For the Study Of Pain Defines mentioning
confidence: 99%
“…These nerves may be injured during surgical incision, rib retraction, trocar placement, or suturing. 5,6 Post-thoracotomy pain syndrome is typically described as aching or tenderness and is localized to the area of incision in approximately 82% of cases. 7 Chronic postthoracotomy pain remains a challenge for clinicians, as many treatment and prevention strategies have yielded disappointing results.…”
Section: The International Association For the Study Of Pain Defines mentioning
confidence: 99%
“…In general, neuronal damage in the thoracic surgery area is called neuropraxia, and most of the neuropathy recovers within a short time due to the temporary intercostal nerve crushing injury caused by the spreader. Benedetti et al 6) reported that most patients who lose superficial abdominal reflexes after a thoracotomy recover within a short period of time, and only 10% of the patients report persistent reflex loss for >2 months. If nerve continuity is maintained, the rate of neurological recovery is reported to be 1-3 mm/day, and rapid recovery is possible with transient nerve damage.…”
Section: Discussionmentioning
confidence: 99%
“…A utilização de toracotomia com menor afastamento do gradil costal, e com preservação muscular, minimiza o trauma operatório e pode permitir a mobilização precoce do conjunto hemitórax e cintura escapular. 5 No grupo II da fase I do estudo estes elementos não tiveram aplicação sistemática,…”
Section: Discussionunclassified